The Impact Of Social Commerce and Live-Streaming On Beauty Product Purchase Interests Among Gen Z - Nindi Kamila Indawati; Putri Nabilla Rasidi; Ulin Nikmah; Sandiyanto Sandiyanto (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2026)
The development of digital technology has brought significant changes in consumer behavior, particularly the utilization of social commerce and live streaming features on social media platforms. This study aims to examine the impact of social commerce and live streaming on purchase intentions for beauty products among Generation Z. The method used is a Systematic Literature Review (SLR) with data sources from Google Scholar. The selection process used inclusion and exclusion criteria to identify relevant scientific articles published between 2020 and 2025, resulting in 10 articles for descriptive analysis. The results of the study indicate that social commerce and live streaming generally have a positive and significant effect on purchase intentions for Generation Z towards beauty products. Factors that strengthen this influence include interactivity, product visualization, host or influencer credibility, promotions, and customer reviews. Thus, it can be concluded that digital marketing strategies based on social commerce and live streaming will be more effective if supported by efforts to build consumer trust through credible information and transparent reviews.